2011
DOI: 10.1186/1471-2458-11-613
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference and risk of elevated blood pressure in children: a cross-sectional study

Abstract: BackgroundIncreasing childhood obesity has become a major health threat. This cross-sectional study reports associations between schoolchildren's waist circumference (WC) and risk of elevated blood pressure.MethodsWe measured height, weight, neck and waist circumference, and blood pressure in regular health examinations among children in grade 1 (ages 6-7 years) at six elementary schools in Taipei County, Taiwan. Elevated blood pressure was defined in children found to have mean systolic or diastolic blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 44 publications
(62 reference statements)
5
31
0
5
Order By: Relevance
“…25 In our study, obesity, defined by BMI percentile, was more highly correlated with high PP (defined as being in the 4th quartile), but after multivariable adjustment we found it did not have an independent association of a greater likelihood of having a higher PP suggesting the association is mediated by other factors. However, WC, a measure of central obesity, which is another risk factor for CV disorders, 16-18 was independently associated with a significantly increased likelihood of having a PP in the 4th quartile. Studies by Mehta et al revealed that, although WC and BMI were independent predictors of left ventricular mass index, WC predicted altered left ventricular function better than BMI in children between the ages of 3–19 years.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…25 In our study, obesity, defined by BMI percentile, was more highly correlated with high PP (defined as being in the 4th quartile), but after multivariable adjustment we found it did not have an independent association of a greater likelihood of having a higher PP suggesting the association is mediated by other factors. However, WC, a measure of central obesity, which is another risk factor for CV disorders, 16-18 was independently associated with a significantly increased likelihood of having a PP in the 4th quartile. Studies by Mehta et al revealed that, although WC and BMI were independent predictors of left ventricular mass index, WC predicted altered left ventricular function better than BMI in children between the ages of 3–19 years.…”
Section: Discussionmentioning
confidence: 90%
“…12-15 There are several anthropometric measures that help to determine the differences in body fat distribution such as body mass index (BMI), waist circumference (WC), waist to height ratio, and waist to hip ratio that were shown to have an independent relationship to CV risk factors during childhood. 16-18 However, to date there are no studies that have looked at the association between PP and body fat indices such as obesity based on BMI and WC, a measure of central obesity, in children.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TBF was modestly related to both systolic and diastolic blood pressures. Indeed Choy et al, 28 showed an association between increased WC and raised blood pressure. Although several studies have shown that a larger HC is protective against HT and metabolic diseases 29,30 , our study showed such protection in males only while larger HC was associated with higher blood pressure in females.…”
mentioning
confidence: 99%
“…WC is considered as the most important anthropometric factor associated with the hypertensive risk (Siani et al 2002). (Choy et al 2011). WC correlates better with visceral adipose tissue and is a better predictor of cardiovascular disease than are BMI and waist-to-hip ratio (Okosun et al 1998).…”
Section: Resultsmentioning
confidence: 99%